Selection of the method of linear ordering using the example of assessing the level of socio-economic development of European Union countries - Sompolska-Rzechuła, Agnieszka (Wybór metody porządkowania liniowego na przykładzie oceny poziomu rozwoju społeczno-gospodarczego krajów Unii Europejskiej, 2019)
The aim of the article is to present the issues of choosing the optimal procedure for the linear ordering of objects and assessing the correctness of the selected methods of the linear ordering. The goal was achieved by creating linear ordering of objects using various methods for normalizing the value of diagnostic features. An aggregate measure based on various properties of the synthetic feature was used to select the optimal ordering, among others, the compatibility of the mapping, the correlation of the synthetic line variable with diagnostic variables, the rank correlation of the synthetic variable with diagnostic variables and the variability of the synthetic variable. The study was conducted based on the example of data concerning 28 European Union countries according to the level of socio-economic development in the context of sustainable development concerning society, economy and the environment. The linear ordering of countries using the quotient transformation with an arithmetic mean turned out to be the most correct ordering
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 118-129
Keywords: linear ordering; optimal method; normalization of diagnostic features; liniowe porządkowanie; optymalna pocedura; normalizacja cech diagnostycznych